Optimasi Pretreatment Asam Organik dan Anorganik terhadap Karakteristik Fisikokimia, Kekuatan Gel, dan Profil FTIR Gelatin Tulang Ikan Tenggiri (Scomberomorus sp.) - Andi Pratama; Siti Rahmawati (Insight of Biology, 2026)
Gelatin is a biopolymer obtained through the partial hydrolysis of collagen and is widely utilized in the food, pharmaceutical, and cosmetic industries. This study aimed to evaluate the effects of acid type and concentration during the pretreatment process on the physicochemical characteristics, gel strength, and FTIR profile of gelatin extracted from Spanish mackerel (Scomberomorus sp.) bones, as well as to determine the optimum pretreatment condition for producing high-quality gelatin. Spanish mackerel bones collected from a fish processing industry in Ampenan Village, Mataram City, West Nusa Tenggara, Indonesia, were subjected to pretreatment using two types of acids, namely hydrochloric acid (HCl) and citric acid, each applied at three different concentrations. The evaluated parameters included yield, moisture content, ash content, pH, viscosity, gel strength, and functional group characterization using Fourier Transform Infrared (FTIR) spectroscopy. The results demonstrated that pretreatment with 4% HCl produced the highest quality gelatin, with a yield of 9.48%, moisture content of 7.72%, ash content of 0.86%, pH of 4.82, viscosity of 6.20 cPs, and gel strength of 163.63 g Bloom. All measured parameters complied with the requirements of the Indonesian National Standard (SNI 06-3735-1995) for gelatin. FTIR analysis confirmed the presence of amide A, B, I, II, and III absorption bands, indicating the characteristic collagen-derived structure of gelatin. Therefore, pretreatment with 4% HCl was identified as the optimum condition for extracting gelatin from Spanish mackerel bones.